Pemanfaatan Tumbuhan Sebagai Makanan Khas Aceh di Banda Aceh - Muslich Hidayat (Universitas Syiah Kuala, 2009)
The utilization of plants as traditional Aceh food is a hereditary action for generations. Today, there are some tendencies that the knowledge of traditional Aceh food is declining. Various foreign and instant foods which enter Aceh are one of the tendency causes. The circumstance in Aceh which is not conducive makes many variety of plants in the forest are no longer use. The missing generation as an effect of earthquake and tsunami disaster happened in Aceh brings possibility of loosing knowledge of traditional Aceh food.This research aims to make a proposal of plants utilizing management as material of traditional Acehn food from local knowledge to be sustained for generations in Banda Aceh. It can be conducted in: (1) knowing the kinds of plants used for Aceh food by society. (2) Knowing the value and contribution of utilizing plants as traditional Aceh food for society. This research conducted from June to August 2005, continued in January until March 2006.The collecting of data conducted in two villages. They are in Lam Ara village in Banda Raya sub district and Darussalam village in Syiah kuala sub district. The technique of data collecting is with interview, intake of plants sample in field and field observation. Determining of responder conducted with the random stratification sampling method which is divided into three groups.Result of research indicate that there are 118 plant type consisted of 43 familia. Among 43 familia from plant used in traditional Aceh food, there are 5 familia which its use most often. They are Fabaceae, Rutaceae, Solanaceae, Rubiaceae And Euphorbiaceae. Among plants used by society there are 16 kinds of plants have been generated intensively, 25 kinds are not intensively generated, 36 kinds is obtained from forest or wild nature. And 23 kinds of plant utilized come from outside area. This result is obtained from 51 kinds of Traditional Aceh food. Potential Plant developed among other things are shallot ( Allium Cepa L.) with the value of plant utilizing at food is more than 28 food, garlic ( Allium Sativum L.), red pepper ( Capsicum Annum L.), and coconut ( Cocos Nucifera L.) with the value of plants utilizing is between 22 to 28 at traditional Aceh food.